The impact of individual differences on investigative hypothesis generation under time pressure - Kim, Sunghwan (International journal of police science & management, 2020)
When decisions are made under time pressure, individuals tend to reduce the number of hypotheses generated to explain and solve problems. This research investigates the extent to which individual differences in (a) domain-specific experience, (b) fluid intelligence, (c) need for closure (NFC), and (d) time urgency moderated the effect of time pressure on investigative hypothesis generation. Korean detectives (N = 133) participated in simulated investigative scenarios. To induce the perception of time pressure, one group was informed that the task would have to be completed under time pressure (N = 66), whereas the other group did not receive this instruction (N = 67); although both groups had the same amount of time). Outcomes included the number and quality of hypotheses generated for solving the case. The quality of hypotheses generated was measured against criteria established by expert detectives. Results revealed that time pressure directly decreased the quantity and quality of hypotheses generated. In the relationships, low time urgency moderated the effect of time pressure on the number and quality of hypotheses generated, also low NFC moderated the impact of time pressure on the number of hypotheses generated. Furthermore, the most experienced detectives were least affected by the negative association between time pressure and the quality of hypotheses generated. The findings suggest lower time urgency, lower NFC and more experience are adaptive ‘protective’ factors against the negative impact of time pressure on hypothesis generation within high stakes and uncertain situations such as rape investigations.